2011
DOI: 10.1073/pnas.1111650108
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus high fidelity variant loses fitness in mosquitoes and mice

Abstract: The error rate of RNA-dependent RNA polymerases (RdRp) affects the mutation frequency in a population of viral RNAs. Using chikungunya virus (CHIKV), we describe a unique arbovirus fidelity variant with a single C483Y amino acid change in the nsP4 RdRp that increases replication fidelity and generates populations with reduced genetic diversity. In mosquitoes, high fidelity CHIKV presents lower infection and dissemination titers than wild type. In newborn mice, high fidelity CHIKV produces truncated viremias an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
288
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(304 citation statements)
references
References 35 publications
10
288
3
3
Order By: Relevance
“…3c). This indicated that the amino acid substitutions in nsp9 affected PRRSV fitness in vitro, a characteristic which was usually observed in some other RNA virus mutants containing high fidelity RdRp (Coffey et al, 2011;Van Slyke et al, 2015).…”
mentioning
confidence: 60%
“…3c). This indicated that the amino acid substitutions in nsp9 affected PRRSV fitness in vitro, a characteristic which was usually observed in some other RNA virus mutants containing high fidelity RdRp (Coffey et al, 2011;Van Slyke et al, 2015).…”
mentioning
confidence: 60%
“…Second, the enhanced fidelity reduces the frequency of genetic reversion to a wild-type, pathogenic phenotype (12). There is now evidence in several systems that RdRp fidelity is a determinant of viral pathogenesis and virulence (11)(12)(13)(14)(15)(16)(17)(18). Unfortunately, none of the mutations in the RdRp gene that lead to increased replication fidelity are at positions conserved across virus families, making it difficult to extrapolate attenuation by enhanced fidelity to other systems.…”
mentioning
confidence: 99%
“…A large increase in the mutation rate can create strong selection pressure for a lowered mutation rate, and a reduction in the mutation rate may thus evolve in short order. Our own work with a mutator strain of Escherichia coli and a nucleoside analogue mutagen, together with several previous mutagenesis studies using different viral systems, shows that resistance to mutagens at high doses can evolve rapidly and through a number of different mechanisms [76][77][78][79][80][81][82]. If one could increase the mutation rate to a level that is high enough to cause extinction, but not too high, selection for resistance could, in principle, be reduced considerably and the evolution of resistance might be prevented.…”
Section: Sufficient and Necessary Conditionsmentioning
confidence: 90%